2021
DOI: 10.3389/fcomp.2021.656873
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Behavior Change Theory as Part of Persuasive Technology: A Scoping Review on Social Comparison

Abstract: Theories from psychology or the social sciences are commonly used as a starting point when designing persuasive technologies that aim to evoke a specific behavior change. Ideally, using these theories would (1) help guide the design of the persuasive technology and (2) help evaluate and inform the theory. In this paper, we focused on the first aspect and looked at how papers report on how a theory guided the design of persuasive technology. We performed a scoping review focused on the operationalization of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent studies have identified a lack of justification and guidance for the operationalization of BCTs ( Fulton et al, 2018 ; Lemke and de Vries, 2021 ). The evidence indicates that the way BCTs such as social support are incorporated into interventions could affect how they are associated with engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified a lack of justification and guidance for the operationalization of BCTs ( Fulton et al, 2018 ; Lemke and de Vries, 2021 ). The evidence indicates that the way BCTs such as social support are incorporated into interventions could affect how they are associated with engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In return, employees may increase their efforts and extend their working time; this simultaneously reduces mental fatigue at the workplace. Lemke and Vries (2021) pointed out that social comparison theory can tap into the potential positive or negative effects on individual behavior to explain the reasons for behavior change. This theory provides ideas and a basis for this study to deeply explore the hypothesis related to the causes of employees’ mental fatigue.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%